2017
DOI: 10.1186/s13052-017-0335-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis in young children less than 5 years: review article

Abstract: Despite wide spread availability of sophisticated diagnostic imaging, acute appendicitis in pre-school children remains a diagnostic challenge. Most of these children present late, often with complications e.g. appendicular perforation, abscess formation and peritonitis and as result hospital stay is prolonged and is associated with increased morbidity and mortality.The purpose of this article is to review peculiar features of acute appendicitis in preschool children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
163
0
23

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(189 citation statements)
references
References 93 publications
3
163
0
23
Order By: Relevance
“…Delayed intervention leads to dramatic complications such as perforation and abscess formation while rushing to surgery is associated with a high negative appendectomy of up to 15%–30% 2. Diagnosis of appendicitis in children is challenging, not only because there are so many other nonsurgical conditions that mimic appendicitis,1 but also because there are difficulties in communication and examination 3…”
Section: Introductionmentioning
confidence: 99%
“…Delayed intervention leads to dramatic complications such as perforation and abscess formation while rushing to surgery is associated with a high negative appendectomy of up to 15%–30% 2. Diagnosis of appendicitis in children is challenging, not only because there are so many other nonsurgical conditions that mimic appendicitis,1 but also because there are difficulties in communication and examination 3…”
Section: Introductionmentioning
confidence: 99%
“…The ease of perforation in this age group is associated with some peculiar anatomical features such as thin‐walled appendix and inadequate omental barrier. A recent report has pegged the rate of missed diagnosis in children of 3 years and below at 70%‐100% and further revealed that as age decreases, there is a 5‐fold increase in the risk of developing appendicitis complication as a consequence of misdiagnosis . Clinical manifestations of sepsis before appendectomy surgery, including abnormal body temperature, tachycardia, tachypnea, WBC < 5000 or more than 15 000, and abnormal forms of tuberculosis .…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptom is abdominal pain. About 1%‐8% of children with abdominal pain have acute appendicitis . In children younger than 3 years, fever, diarrhea, and vomiting are the most common symptoms of appendicitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pediatric patients are most frequently affected (60%), probably reflecting a difference in the pathological aspects of this condition between both groups. While in adults the omentum can contain the inflammation affecting the appendix, in children the omentum is underdeveloped and unable to limit purulent leakage [10, 11]. Thus, children are more prone to develop peritonitis compared to adult patients.…”
Section: Discussionmentioning
confidence: 99%